THE EFFECTIVENESS OF THE INTERVENTION OF COVID-19 PREVENTION IN THE ELDERLY: SYSTEMATIC REVIEW - Bernand Gamaliel Fa Atulo (Jurnal Medika Hutama, 2022)
All countries in the world are still struggling in the face of the Coronavirus Disease 2019 (COVID-19) pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). The COVID-19 pandemic is a serious threat to all age groups, especially the elderly. The disease prevention strategy continues to be carried out for the elderly group in order to reduce morbidity and mortalitas rate. This study uses a systematic review approach which is carried out by searching for literature related to the topic taken. Search literature using ScienceDirect and PubMed from 2020-2021 and meet the inclusion criteria so that six eligible literatures are obtained. The various study literatures provide information on the description and results of preventive interventions in the elderly group in the midst of the COVID-19 pandemic.